Characterization of Natural Ventilation Systems in Residential Buildings in Portugal - The Importance of Standardization - Pinto, Manuel (2014)
The technical recommendations regarding ventilation in various countries propose average rates of one hourly renewal in main rooms (bedrooms and living/dining rooms) and four renewals per hour in service rooms (kitchens and bathrooms). Most recently built residential buildings in Portugal may not comply with these rates. The adoption of “general and permanent ventilation” systems is essential. A survey was conducted in the spring of 2000 with the purpose of characterizing the ventilation systems of residential buildings under construction. Questionnaires were sent to 6700 construction companies in the northern region. Answers were obtained regarding 2700 dwellings, the main conclusions of which are presented in this article. The implications of prNP 1037-1: “Ventilation and combustion products evacuation from places with gas-burning appliances, Part 1: Dwellings, Natural ventilation” project are also analyzed.